CONTAGION EFFECT ANTAR NEGARA ASEAN-5 - R Adisetiawan; Ahmadi Ahmadi (Universitas Batanghari, 2018)
This study was conducted to determine whether there is a contagion effect on the stock exchanges among ASEAN-5 countries (Indonesia, Singapore, Malaysia, Thailand and Philippines) during 2001.1 - 2018.5 period using the monthly return data of the five ASEAN-5 stock exchanges. This study uses granger causality test to see the direction of mutual influence that indicates the existence of contagion effect. The results revealed that the Indonesian stock exchange has a mutually influential relationship with the Thai stock exchange.